Draft Annual Plan 2003-04 Haryana State - Planning Commission (Planning Commission, 2003)
An outlay of Rs. 2034.00 crore has been approved for the Annual Plan 2002- 2003. While distributing this outlay among various sectors, development of infrastructure of irrigation, power, roads and road transport has been given the highest priority followed by social services sector. An outlay of Rs. 930.90 crore which is 45,8% of the total proposed plan outlay of Rs. 2034.00 crore has been allocated for the improvement/extension of the basic infrastructure of irrigation, power, roads and road transport. Irrigation sector has been provided an amount of Rs. 334.50 crore (16.5%) which includes an outlay of Rs. 60.00 crore of World Bank Aided, Water Sector Reforms Project (WRCP Phase-II)” Roads and road transport development has been allocated an outlay of Rs. 335.00 crore (16.5%) The generation, transmission and distribution of power have been allotted an outlay of Rs. 261.40 crore which is 12.8% of the total plan outlay.
Planning Department, Government of Haryana